Factors Associated with the Level of Non-Adherence to Take Antituberculosis drugs - Garuda Nusantara Putra Utomo; Helmia Hasan; Sulistiawati Sulistiawati (State University of Gorontalo, 2023)
Non-adherence to take antituberculosis drugs is one of the causes of tuberculosis (TB) resistance. However, in Indonesia no study identified the factors associated with the level of non-adherence to take antituberculosis drugs in Multi-Drug Resistant Tuberculosis (MDR-TB) patients when they were still pulmonary drug-sensitive TB survivors. The aim of this study was to identify factors associated with the level of non-adherence to take antituberculosis drugs. This was a cross-sectional study which was conducted from October 2021 to December 2021 at Dr. Soetomo Hospital Surabaya. The dependent variable was the level of non-adherence to take antituberculosis drugs, while the independent variables were age, gender, education level, income, distance from home to health care service, role of health workers, role of superintendent of swallowing drugs (PMO), and side effects. Forty out of the 195 secondary-resistant MDR-TB patients were selected as subjects for this study based on their willingness. The instrument was questionnaire which had been tested for its validity and reliability. The results of bivariate analysis showed that gender, the role of PMO, and side effects had a significance of p0.05. The results of the bivariate analysis indicated that gender, role of PMO, and side effects have significance value p0.05. The conclusion of this study is gender, role of PMO, and side effects are associated with the level of non-adherence to take antituberculosis drugs.